Linear algebra with applications - Williams, Gareth, 1937- (The Jones and Bartlett Publishers series in mathematics. Linear algebra, 2011)
Revised and edited, Linear Algebra with Applications, Seventh Edition is designed for the introductory course in linear algebra and is organized into 3 natural parts. Part 1 introduces the basics, presenting systems of linear equations, vectors and subspaces of R, matrices, linear transformations, determinants, and eigenvectors. Part 2 builds on this material, introducing the concept of general vector spaces, discussing properties of bases, developing the rank/nullity theorem and introducing spaces of matrices and functions. Part 3 completes the course with many of the important ideas and methods of numerical linear algebra, such as ill-conditioning, pivoting, and LU decomposition. Offering 28 core sections, the Seventh Edition successfully blends theory, important numerical techniques, and interesting applications making it ideal for engineers, scientists, and a variety of other majors. The Student Solutions Manual to Accompany Linear Algebra wit Applications, Seventh Edition, is designed to help you get the most out of your linear algebra class. It provides the answers to selected exercises in each chapter of the textbook. This manual will help you to assess the progress you are making in understanding the concepts presented in each chapter.